Death of a salesman [compact disc] - Miller, Arthur, 1915-2005 (Audio theatre series., 2011)
A searing portrait of the physical, emotional, and psychological costs of the American dream. Willy Loman is the iconic traveling salesman, whose family is torn apart by his desperate obsession with greatness and social acceptance. As his two sons cast about aimlessly for their stations in life, Willy begins to come unraveled when the reality of his life threatens his long-cherished illusions.